Comparative study of somatic and motor characteristics of the first 100 hammer throw athletes all time - Ivan, P.; Gheroghe, D. (Science, Movement & Health, 2017)
Aim. Study bibliography. The collection and tabulation of the following parameters: performances, age, height and weight on the first 100 hammer throw athletes seniors outdoors all time. Processing statistical and mathematical data specified above, regarding the following indicators: number of cases, maximum value, minimum value, amplitude, mode, median, average, quartile 1, 3, quartile difference, dispersion, average of absolute deviation, standard deviation, coefficient of variation and correlation. Evaluation of the results and their interpretation. Methods. As a research method we have used the case study, observation, statistics and graphics. Results. After data processing have resulted 2 summary tables and 4 graphs. Conclusions. The average performances is 82.45 m for men and 72.68 m for women. The average age is 28.63 years for men and 26.54 years for women. The average height is 188.03 cm for men and 175.60 cm for women. The average weight is 112.09 kg for men and 84.81 kg for women